2016
DOI: 10.1210/en.2016-1141
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Neuropeptide B (NPB), Neuropeptide W (NPW), and Their Receptors in Chickens: Evidence for NPW Being a Novel Inhibitor of Pituitary GH and Prolactin Secretion

Abstract: The 2 structurally and functionally related peptides, neuropeptide B (NPB) and neuropeptide W (NPW), together with their receptor(s) (NPBWR1/NPBWR2) constitute the NPB/NPW system, which acts mainly on the central nervous system to regulate many physiological processes in mammals. However, little is known about this NPB/NPW system in nonmammalian vertebrates. In this study, the functionality and expression of this NPB/NPW system and its actions on the pituitary were investigated in chickens. The results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 56 publications
2
45
1
Order By: Relevance
“…The name of NPW is derived from tryptophan residues (single-letter code W) as it appears in both the terminal N- and C- in its two mature forms ( Takenoya et al, 2012 ). Abundance of both these isoforms were demonstrated in several species including human, rat, mouse, pig, and chicken ( Brezillon et al, 2003 ; Tanaka et al, 2003 ; Kitamura et al, 2006 ; Fang et al, 2015 ; Bu et al, 2016 ). Chicken NPW exerts a noteworthy structural conservation with NPW of mammals ( Figure 1 ; Bu et al, 2016 ).…”
Section: Structurementioning
confidence: 99%
See 1 more Smart Citation
“…The name of NPW is derived from tryptophan residues (single-letter code W) as it appears in both the terminal N- and C- in its two mature forms ( Takenoya et al, 2012 ). Abundance of both these isoforms were demonstrated in several species including human, rat, mouse, pig, and chicken ( Brezillon et al, 2003 ; Tanaka et al, 2003 ; Kitamura et al, 2006 ; Fang et al, 2015 ; Bu et al, 2016 ). Chicken NPW exerts a noteworthy structural conservation with NPW of mammals ( Figure 1 ; Bu et al, 2016 ).…”
Section: Structurementioning
confidence: 99%
“…Such modification is unique among the mammalian bioactive peptides and its biological significance remains to be clarified, while the brominated and unbrominated forms of NPB exert comparable functional activities ( Fujii et al, 2002 ; Sakurai, 2013 ). In chicken, NPB precursor produces a mature peptide of 28 amino acids that is different from the 23- or 29 amino acids NPB of mammals ( Bu et al, 2016 ). Additionally, mammalian and avian NPB differ in their N termini where mammals have a “WYK” motif however birds have “WYR” motif.…”
Section: Structurementioning
confidence: 99%
“…Growth hormone (Gh), a single chain polypeptide hormone secreted from Gh cells in the anterior pituitary, plays important roles in the growth and development of vertebrates. Previous studies has established that the secretion of Gh is regulated by many neuroendocrine factors produced by the brain (especially the hypothalamus), including stimulators like Gh-releasing hormone ( 36 ) and ghrelin ( 37 ), and inhibitors like somatostatin (SS) ( 36 ) and neuropeptide W ( 38 ). Recently, it has been shown that Oxt stimulates GH release possibly directly via Oxtr in the pituitary of rats ( 10 ), adding a new player in the list of neuroendocrine factors regulating Gh cell functions.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropeptides W, NPB and their receptors are mainly expressed in the central and periphery issues, which are involved in many physiological processes, including inflammatory pain, energy homeostasis, cardiovascular functions, immune system, stress and the neuroendocrine and respiratory systems . Previous studies have detected NPW/NPB mRNA, including bone marrow, femur and costal cartilagein, in humans, rats, pigs and chickens . The effect of G protein activation was mediated by protein kinase A (PKA), protein kinase C (PKC) and the mitogen‐activated protein kinases (MAPKs) cascades reaction .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Previous studies have detected NPW/NPB mRNA, including bone marrow, femur and costal cartilagein, in humans, rats, pigs and chickens. 1,7,8 The effect of G protein activation was mediated by protein kinase A (PKA), protein kinase C (PKC) and the mitogen-activated protein kinases (MAPKs) cascades reaction. 9,10 The down-regulation or inhibition of PKA and PKC blocks chondrogenesis.…”
Section: Introductionmentioning
confidence: 99%